Utilizing co-products of the sweet sorghum-based biofuel industry as livestock feed in decentralized systems - Rao, P.S.; Reddy, B.V.S.; Reddy, R.C.; Blümmel, Michael; Kumar, A.A.; Rao, P.P.; Basavaraj, G. (Food and Agriculture Organization of the United Nations, 2012)
Sweet sorghum-based decentralized crushing and syrup-making units are a major component of sweet sorghum value chains in India. Apart from the main product, syrup, there are several co-products, including grain, bagasse,vinasse, steam, foam and froth. This chapter looks at the state of the art in utilization of these products in livestock feed, as well as exploring emerging opportunities. If the policy framework of the country supports decentralized models, this co-products utilization not only improves economic viability but also has environmental benefits by way of reduced greenhouse gas (GHG) emissions, which are yet to be quantified.